Determinan Hasil Investasi, Klaim dan Tata Kelola Perusahaan Terhadap Solvabilitas Perusahaan Asuransi Jiwa Shariah di Indonesia - Fitri Putri; Slamet Haryono (ILTIZAM Journal of Shariah Economics Research, 2023)
The research aims to determine the impact of Sharia Life Insurance Solvency in Indonesia from 2018-2021 both partially and simultaneously. Uses a panel data approach with multiple linier regression analysis where the data is collected from 13 financial sharia life insurance report with 52 samples. The results of the study in partially shows that claim have a negative significant effect, while board of commissioners, and sharia supervisory board have a positive significant effect on solvency sharia life insurance companies however investment return and board of director have no significant effect. In simultaneously the result of the study shows that sharia life insurance companies solvency is influenced by investment return, claim, board of commissioners, board of director and sharia supervisory board. This means that the contribution of the variable investment return, claim, board of commissioners, board of director and sharia supervisory board to solvability is 73% while the remaining 27% is determined by other factors outside the Y1 equation Furthermore, these findings shall be consideration for managers in making policies. This study combines financial ratios and corporate governance in analyzing the solvency determinants of sharia life insurance companies in Indonesia.